Dialysis patients who smoke are more hypertensive, more fluid overloaded and take more antihypertensive medications than nonsmokers - Mihály Tapolyai; Melinda Forró; Zsolt Lengvárszky; Tibor Fülöp (Renal Failure, 2020)
Background Smoking remains a powerful risk factor for death in end-stage renal disease (ESRD) and so is the presence of fluid overload. The relationship between smoking, blood pressure (BP) control and volume overload is insufficiently explored in patients on maintenance dialysis. Methods This is a retrospective cross-sectional cohort study, utilizing existing patients’ data generated during routine ESRD care, including bimonthly protocol bioimpedance fluid assessment of the volume status. Results We analyzed the data of 63 prevalent patients receiving thrice weekly maintenance hemodiafiltration treatments at one rural dialysis unit in Hungary. The cohort’s mean ± SD age was 61.5 ± 15.3 years; 65% male, 38% diabetic, with a mean arterial blood pressure (MAP) 99.5 ± 16.8 mmHg and Charlson score 3.79 ± 2.04. Of these, 38 patients were nonsmokers and 25 smokers. The nonsmokers’ MAP was 94.3 ± 14.0 versus smokers’ 105.9 ± 18.9 mmHg (p: .002); nonsmokers took an average 0.73 ± 0.92 antihypertensive medications vs. 1.73 ± 1.21 for smokers (p: .0001). The distribution of taking more antihypertensive medications is skewed toward a higher number among the smokers (2x5 chi square p: .004). By bioimpedance spectroscopy, nonsmokers had an average 10.93 ± 7.65 percent overhydration (OH) over the extracellular space compared to 17.63 ± 8.98 in smokers (p: .005). Conclusions Smoking may be a significant mediator of not only BP but also of chronic fluid overload in ESRD patents. Additional, larger studies are needed to explore the mechanistic link between smoking and volume overload.